PENGARUH PARTISIPASI ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI (Studi Empiris Pada OPD Kabupaten Siak) - Jun Friday; Taufeni Taufik; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine : 1) the effect of budgetary participation on budgetary slack, 2) the effect of budget goal clarity on budgetary slack, 3) the effect of budgetary participation on budgetary slack with organizational commitment as moderating variable, 4) the effect of budgetary participation on budgetary slack with organizational culture as moderating variable, 5) the effect of budget goal clarity on budgetary slack with organizational commitment as moderating variable, and 6) the effect of budgat goal clarity on budgetary slack with organizational culture as moderating variable. The population in this study was 28 OPD Siak Regency. In this study, the sample used is the 73 respondents were selected using purposive sampling method. This study used primary data by dissemination of the questionnaires. Technical analysis for test hypothesis that used in this study are multiple linear regression analysis and Moderated Regression Analysis (MRA). The analytical tool used in this study was Stastistical Product and Service Solution (SPSS) version 23.0. The result of this research showed that : 1) budgetary participation negative effect on the budgetary slack with significant level of 0.000, 2) budget goal clarity negative effect on the budgetary slack with significant level of 0.005, 3) organizational commitment can be moderate the effect of budgetary participation on budgetary slack with significant level of 0.000, 4) organizational culture can be moderate the effect of budgetary participation on budgetary slack with significant level of 0.000, 5) organizational commitment can be moderate the effect of budget goal clarity on budgetary slack with significant level of 0.000, and 6) organizational culture can be moderate the effect of budget goal clarity on budgetary slack with significant level of 0.000.Keywords : Budgetary Participation, Budget Goal Clarity, Oganizational Commitment, Organizational Culture, Budgetary Slack